2022
DOI: 10.3748/wjg.v28.i45.6328
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal microbiota: A predictor of COVID-19 severity?

Abstract: Coronavirus disease 2019 (COVID-19), caused by a severe acute respiratory syndrome coronavirus 2 infection, has raised serious concerns worldwide over the past 3 years. The severity and clinical course of COVID-19 depends on many factors ( e.g., associated comorbidities, age, etc ) and may have various clinical and imaging findings, which raises management concerns. Gut microbiota composition is known to influence respiratory disease, and respiratory viral infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 157 publications
1
9
0
1
Order By: Relevance
“…COVID-19 and intestinal microbiota can interact with each other ( 39 ). Some studies suggest that intestinal microbiota may be a predictor of COVID-19 severity ( 40 , 41 ). Therefore, regulating intestinal flora seems to be an effective aspect in improving symptoms ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 and intestinal microbiota can interact with each other ( 39 ). Some studies suggest that intestinal microbiota may be a predictor of COVID-19 severity ( 40 , 41 ). Therefore, regulating intestinal flora seems to be an effective aspect in improving symptoms ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…17 Bacteria cause lung injury and affect intestinal function in the host, while regulating intestinal flora helps to control lung infection. 18 Schuijt et al reported that fecal transplantation through oral gavage of normal intestinal flora restored the control of lung infection and the level of cytokines in the lung in mice, demonstrating the contribution of intestinal flora to lung immunity. 19 Therefore, it was of great significance to investigate the intestinal flora of the host during pulmonary infection, and it was an important way to explore the intervention effect and mechanism of therapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Many proposed therapeutic approaches were introduced to target the gut microbiome, such as taking prebiotics, probiotics, and dietary modifications. During Covid19 pandemic, it was found that the gut commensals, such as Faecalibacteriumprausnitzii , Eubacterium , and Bifidobacteriumadolescentis with immunomodulatory potential suspected in COVID 19 patients, even those who were diagnosed with antibiotics (Neag et al., 2022). They were associated with increased inflammatory cytokines and blood markers of tissue damage due to microbial abundance.…”
Section: The Gut Microbiome As a Therapeutic Targetmentioning
confidence: 99%